The experience of newly graduated nurses on their transition to staff nurses - Fong, Niong Moi (Universiti Malaysia Sarawak (UNIMAS), 2013)
The purpose of this study was to explore the transition experience of the novice or newly graduated nurses (NGNs) from Universiti Malaysia Sarawak (UNIMAS). In addition to that, this study also identified the sufficiency of nursing educational program in UNIMAS.